Interactive learning objects as a solution to challenges in basic medical science teaching - L Keiller; A Alblas; J R Foiret; A V Keiller (South African Medical Association, 2022)
Background. As a core component of any health professions curriculum, basic medical science modules facilitate learning of biology, anatomy, histology and physiology content. To redress the challenges of class size and poor tertiary education readiness, interactive learning objects could facilitate learning and enhance engagement between lecturers and students. Objective. To determine whether the use of learning objects in a basic medical science first-year module is an effective tool for enhancing the student learning experience. Methods. A case study research design with mixed methods of data collection was used. Participants provided informed consent for this study. Learning objects were incorporated into a basic medical sciences first-year module in the Faculty of Medicine and Health Sciences, Stellenbosch University, South Africa. A correlation analysis between usage statistics and assessment results was used to determine the academic effectiveness of this intervention. A thematic network analysis identified the barriers and enablers of the intervention. Results. Student attempts at learning objects correlated with a higher assessment outcome for two of the three tutorials. Technical difficulties, timing and assessment format were barriers to learning with the use of learning objects. Enablers to learning included student enjoyment, facilitating understanding of core concepts, adaptation to new ways of learning and formative assessment. The module team received valuable feedback on the constructed learning environment through the qualitative data collected from students within this study. Conclusion. Interactive learning objects are useful and effective tools for facilitating learning in the context of large, diverse first-year health professions education classes.